In the era of disease-modifying antirheumatic drugs, how close are we to treating rheumatoid arthritis without the use of glucocorticoids? - Yagiz, Burcu; Coskun, Belkis Nihan; Pehlivan, Yavuz; Dalkilic, Ediz; Kiraz, Sedat; Yazisiz, Veli; Kalyoncu, Umut (Springer Heidelberg, 2021)
We wanted to see how close we could get to our goal of treating rheumatoid arthritis (RA) without the use of glucocorticoids (GCs) in the disease-modifying antirheumatic drugs (DMARDs) era using real-life data. Established in 2017, the TReasure database is a web-based, prospective, observational cohort for Turkey. As of May 2019, there were 2,690 RA patients recorded as receiving biologic and targeted synthetic DMARDs (bDMARDs and tsDMARDs) therapy. At the start of the bDMARDs or tsDMARDs, patients with follow-up visits of at least 3 months were registered. At the time of registration and the last visit, doses of GCs were recorded and it was determined if the target dose of <= 7.5 mg was achieved. During registration and follow-up, 23.4% of the patients did not receive GCs and 76.5% of the patients received GCs at any time. GCs could be stopped after 59 (25-116) months in 28.4% of these patients, but 71.6% of patients were still using GC. The target GC dose could not be achieved in 18.2% of these patients (n = 352). The rate of continuing to use GC was significantly higher in women, in the elderly, those with rheumatoid factor (RF) positive, with higher Visual Analog Scale (VAS) pain and Disease Activity Score (DAS)-28. The initial GC dose of >= 7.5 mg/day was found to be crucial in not reaching the GC target dose (p < 0.001, OR 39.0 (24.1-63.2)). The initial GC dose of >= 7.5 mg/day, female gender, age, RF positivity, high DAS28, and VAS pain level were all highly related for GC continuation. Despite the use of DMARDs, our data revealed that we are still far from achieving our goal of treating RA without using steroids.
Keywords: DMARDs; Glucocorticoids; Rheumatoid arthritis; Target dose; TReasure